Pengaruh Keterlibatan Orang Tua dalam Peningkatan Prestasi Belajar Peserta Didik - Thahir, Muthahharah; Rachmaniar, Ananda; Thahir, Wahyuni (Universitas Mathla'ul Anwar Banten, 2024)
This study aims to determine the effect of parental involvement in improving students' learning based on students' opinions. This study used descriptive quantitative research methods. This research was conducted in four public junior high schools in Gowa Regency. The study population consisted of grade IX students with a total population of 1428 students. The research sample was determined by purposive sampling by taking 40 students from each school so that the research sample amounted to 160 students. The results showed that based on students' opinions, each indicator in this study basically did affect students' learning achievement. From the results of the study, it was found that the most influential indicator was that parents always motivate and provide advice regarding future plans with a total percentage of 85.63% then 83% in the indicator parents always take the time to ask how things are going at school and the third indicator 81.25% in the statement parents always participate and attend activities organized by the school. Therefore, the school must develop and improve each of these indicators in order to have an optimal influence on student achievement. This study provides recommendations so that schools can play an active role optimally in increasing parental involvement in improving student achievement.